Emergence of highly transparent photovoltaics for distributed applications. Issue 11 (November 2017) - Traverse, Christopher; Pandey, Richa; Barr, Miles; Lunt, Richard
Abstract Solar energy offers a viable solution to our growing energy need. While adoption of conventional photovoltaics on rooftops and in solar farms has grown rapidly in the last decade, there is still plenty of opportunity for expansion. See-through solar technologies with partial light transmission developed over the past 30 years have initiated methods of integration not possible with conventional modules. The large-scale deployment necessary to offset global energy consumption could be further accelerated by developing fully invisible solar cells that selectively absorb ultraviolet and near-infrared light, allowing many of the surfaces of our built environment to be turned into solar harvesting arrays without impacting the function or aesthetics. Here, we review recent advances in photovoltaics with varying degrees of visible light transparency. We discuss the figures of merit necessary to characterize transparent photovoltaics, and outline the requirements to enable their widespread adoption in buildings, windows, electronic device displays, and automobiles. Transparency offers integration routes unavailable to opaque photovoltaics. Here, Lunt and co-workers review recent progress in transparent solar technologies, highlight technical challenges and measurement considerations, and review performance requirements for various applications.